2003
DOI: 10.1159/000072672
|View full text |Cite
|
Sign up to set email alerts
|

Patch Urethroplasty Using a Fascia lata Autograft in Male Rabbits

Abstract: Introduction: Urethral reconstruction is difficult when the genital skin is not available for surgery. We evaluate the feasibility of using the autologous fascia lata as a graft for urethral repair. Materials and Methods: 10 male rabbits underwent urethroplasty after creation of a ventral urethral defect. The defect was repaired using a graft harvested from the fascia lata. The animals were divided into three groups and sacrificed at 2, 4 and 12 weeks postoperatively. Radiologic control was performed after 10–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
2
5
1
Order By: Relevance
“…All dogs had non‐obstructive urine outflow with a normal frequency of urination. Further, the new urethral tissue was histologically and functionally similar to the native urethra, a finding also reported in rabbits 20 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…All dogs had non‐obstructive urine outflow with a normal frequency of urination. Further, the new urethral tissue was histologically and functionally similar to the native urethra, a finding also reported in rabbits 20 …”
Section: Discussionsupporting
confidence: 78%
“…Use of fascia lata (FL) within the urinary tract has been reported in rabbits 20 . Thus, we were interested in determining whether FL autograft could be used for repairing urethral defect in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study on ten rabbits, Campodonico et al [13] have carried out fistula repair using allograft FL and have stated an 80% success rate. Nanni et al [14] had used free peritoneal grafts in 12 rabbits and reported 67% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…3,19,20 Several techniques to restore the normal urethral lumen, when the defect is too large to be closed primarily without tension, have been described. Genital and extra genital skin grafts, 21,22 buccal mucosa, 23,24 bladder mucosa grafts, [25][26][27] intestinal submucosa, 28,29 vascularized tunica vaginalis flaps, 30 free colonic mucosa, 31 fascia lata, 32,33 tubularized peritoneal graft, 34 carotid artery, 35 and jugular vein 36 have all been described. Most of the procedures have been described in human surgery, [21][22][23][24][25][26][27][30][31] some have been described in dogs, 29,33,[35][36] and several have been described in rabbits.…”
mentioning
confidence: 99%
“…Most of the procedures have been described in human surgery, [21][22][23][24][25][26][27][30][31] some have been described in dogs, 29,33,[35][36] and several have been described in rabbits. 28,32,34 Vaginourethroplasty has also been performed successfully on a female cat with multiple pelvic fractures. 37 Recently, a novel technique that uses an ischial ostectomy to reduce tension at the site of urethral anastomosis has been described in cadaveric dogs.…”
mentioning
confidence: 99%